ChemInform Abstract: A Critical Review on in situ Reduction of Graphene Oxide During Preparation of Conducting Polymeric Nanocomposites. Issue 27 (18th June 2015) - Mural, Prasanna Kumar S.; Sharma, Maya; Madras, Giridhar; Bose, Suryasarathi
Abstract Review: 52 refs.